Factors Influencing Business Success: Basis for Entrepreneurs Strategy: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study analyzes the factors influencing business success: basis forentrepreneurs strategy. Many entrepreneurs do not succeed in the business field; in addition,in this study, there are many factors that can help entrepreneurs avoid failure.The results showed that all of the factors, money, manpower, machine, and management,strongly agree on influencing business success based on their experience in running theirbusinesses. Also, the results revealed that they encountered a lot of difficulties, and theyfound solutions to solve the problem.This study could be used to find the factors that can influence business success and provide astrategy that can be used to solve the business's problems.
Keywords: Business